2020
DOI: 10.1186/s13027-020-00293-9
|View full text |Cite
|
Sign up to set email alerts
|

Management guidelines of penile cancer- a contemporary review of sub-Saharan Africa

Abstract: Background Penile cancer is a rare malignancy with prevalence higher in areas of high Human Papilloma Virus (HPV) such as Africa, Asia and South America. In middle- and low-income countries where circumcision is not routinely practiced, the rate of penile cancer could be ten times higher. Main body of the abstract A literature review was conducted from 1992 to 2019 using PubMed, Google Scholar, African Journal Online and Google with inclusion of 27 publications with emphasis on the Sub-Saharan literature. Fin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(22 citation statements)
references
References 21 publications
1
21
0
Order By: Relevance
“…A similar situation is seen across numerous regions of Africa, where eight countries — Eswatini, Botswana, Uganda, Burundi, Zambia, Zimbabwe, Lesotho and Rwanda — are among the ten countries in the world most affected by penile cancer, according to the WHO 1 , with an ASR of >1.3 for each country. A major concern in those countries is the delayed consultation time, which often reaches 21 months 34 from the onset of the disease to physician evaluation, leading to alarming rates of locally invasive disease (T2–4) 35 , whereby up to 50% of patients present with T3 disease and almost 20% with nodal involvement at diagnosis 33 . Moreover, a lack of the availability of appropriate chemotherapy and radiotherapy treatments further worsens the prognosis of penile cancer in these countries 36 .…”
Section: A Need For Collaboration and Centralizationmentioning
confidence: 99%
“…A similar situation is seen across numerous regions of Africa, where eight countries — Eswatini, Botswana, Uganda, Burundi, Zambia, Zimbabwe, Lesotho and Rwanda — are among the ten countries in the world most affected by penile cancer, according to the WHO 1 , with an ASR of >1.3 for each country. A major concern in those countries is the delayed consultation time, which often reaches 21 months 34 from the onset of the disease to physician evaluation, leading to alarming rates of locally invasive disease (T2–4) 35 , whereby up to 50% of patients present with T3 disease and almost 20% with nodal involvement at diagnosis 33 . Moreover, a lack of the availability of appropriate chemotherapy and radiotherapy treatments further worsens the prognosis of penile cancer in these countries 36 .…”
Section: A Need For Collaboration and Centralizationmentioning
confidence: 99%
“…In Africa, the lack of diagnostic tool, poor health seeking behavior and poverty have been a barrier to both diagnosis and treatment of UCs [ 23 ]. Contemporary reviews from Sub-Saharan Africa have revealed much later stages of presentation of other rare genitourinary cancers including penile and testicular tumor [ 24 , 25 ]. To date, the available literature on UC of the upper tract or urethra remains sparse.…”
Section: Discussionmentioning
confidence: 99%
“…World J Oncol. 2021;12(1): [20][21][22][23][24][25][26][27] and excision of the bladder cuff because of a considerable risk of tumor recurrence in this area. There is strong evidence to suggest that adjuvant instillation of mitomycin within 72 h of surgery can reduce the recurrence rate within the first year [2,9,10].…”
Section: Rare Urogenital Cancersmentioning
confidence: 99%
“…Penile malignancy is rare worldwide, with developed countries in Europe and America reporting incidences of less than 1 case per 100,000 men annually [ 1 , 2 ]. However, the situation is dissimilar in developing countries of sub-Saharan Africa, parts of Asia and Latin America where relatively high incidence rates have been reported.…”
Section: Introductionmentioning
confidence: 99%
“…Most cases present between 50 and 70 years of age, with majority of cases in sub-Saharan Africa presenting in the advanced stages of the disease, associated with a five-year survival rate of 50%. When pelvic lymph nodes are involved, survival may approach 0% [ 2 , 5 ]. Most cases presents with a lesion on the glans (48%), followed by the prepuce (21%), on the prepuce and glans (15%), coronal sulcus (6%) and penile shaft (<2%).…”
Section: Introductionmentioning
confidence: 99%